2005
DOI: 10.1063/1.1849511
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of vortex configuration by honeycomb hole arrays in a superconducting Nb film

Abstract: Determination of T c , vortex creation and vortex imaging of a superconducting Nb film using low-temperature magnetic force microscopy A honeycomb array of submicrometer holes in a Nb superconducting thin film has been fabricated to investigate the flux pinning effect. It is found that the minima positions reveal two regimes characterized by the matching fields and the fractional ones. It is believed that the complex behavior may come from more than one vortex being captured per pinning site. Furthermore, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 11 publications
5
28
1
Order By: Relevance
“…2 is very similar to the experimental results observed for honeycomb arrays in Ref. [33]. In the experiments, strong commensuration effects appeared at B/B that the commensuration effects at B/B H φ = 3 and 4 are very weak or absent while those at B/B H φ = 3.5 and 4.5 are very pronounced.…”
Section: Simulationsupporting
confidence: 78%
See 3 more Smart Citations
“…2 is very similar to the experimental results observed for honeycomb arrays in Ref. [33]. In the experiments, strong commensuration effects appeared at B/B that the commensuration effects at B/B H φ = 3 and 4 are very weak or absent while those at B/B H φ = 3.5 and 4.5 are very pronounced.…”
Section: Simulationsupporting
confidence: 78%
“…In Ref. [33], it was also observed that for fields greater than the second matching field, B/B φ > 2, the commensuration effects at half-integer matching fields become more prominent than those at integer matching fields. This effect can be understood by considering that since the honeycomb pinning array is simply a triangular pinning array that has been diluted by 1/3, the field B/B φ = 1.5 for the honeycomb array would correspond to an integer matching field B/B φ = 1 in a triangular array of the same density.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, extensive molecular dynamics simulations have been conducted in recent years 21 , which revealed remarkable variety of static and dynamic phenomena at integer and noninteger fillings. Experimental studies have also been performed recently, showing unusual features of such superconducting systems such as guided vortex motion [25][26][27][28] . In combination with computer simulations, we reveal that interstitial vortices appear once the saturation number n si predicted for an isolated defect is exceeded.…”
mentioning
confidence: 99%